A Study on Inflation: Reason Behind Rising Price of Construction Materials in Johor Bahru - Samsir, Muhammad Syuaib; Khalid, Zailawati; Attan, Norazah; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2023)
Inflation is one of the familiar words in economic and has been plunging countries across the world, making it become the long period of instability. It also become one of the important indicators for economic conditions. The shift in the inflation rate can be a problem to calculate it and track the monetary policies on time. The inflation can affect various sectors including the construction industries. The rising price of construction materials affected by the rate of inflation of the country. The purposes of this study are to find on how the inflation affected the construction materials. The study also being conducted in order to find the reason behind the rising price of construction materials and to study the strategies that being by contractors in order to adapt with the rising price of construction materials. For this study, the data collection used the quantitative method where surveys using questionnaire being produced and distributed to 250 respondents but only 81 respondent’s response with the questionnaire. The population of G5, G6 and G7 that are registered under the CIDB and active with managing and handling construction projects in Johor Bahru. the collected data will be analyzed using Statistical Package for the Science Social (SPSS). Data being collected being tabulated into descriptive and reliability test to identify reliability of each objective. Data being presented in the form of tables, chart and graph. From the result of the study, the researchers find that the inflation raised the contractors’ cost of borrowing to the banks such as loans, makes the interest rate become high, increasing projects budgets, eroding the purchasing power of the contractors and creating cost overrun.